A meta-analysis of ursodeoxycholic acid therapy versus combination therapy with corticosteroids for PBC-AIH-overlap syndrome: evidence from 97 monotherapy and 117 combinations - Zhang, Huawei; Li, Sainan; Yang, Jing; Zheng, Yuanyuan; Wang, Jianrong; Lu, Wenxia; Zhou, Yuqing; Yin, Qin; Zhu, Rong; Guo, Chuanyong (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
In this study, a meta-analysis of randomised controlled trials that compared ursodeoxycholic acid (UDCA) monotherapy with therapies combining UDCA and corticosteroids was performed. We found that combination therapy with UDCA and corticosteroids was more effective than UDCA monotherapy for primary biliary cirrhosis-autoimmune hepatitis-overlap syndrome.